Investigation of and Strategies to Control the Final Cluster of the 2018–2020 Ebola Virus Disease Outbreak in the Eastern Democratic Republic of Congo. (23rd September 2022) - Keita, Mory; Polonsky, Jonathan; Finci, Iris; Mbala-Kingebeni, Placide; Ilumbulumbu, Michel Kalongo; Dakissaga, Adama; Ngwama, John Kombe; Tosalisana, Michel Kasereka; Ahuka-Mundeke, Steve; Gueye, Abdou Salam; Dagron, Stephanie; Keiser, Olivia; et al.
Abstract: Background: On April 10, 2020, while the independent committee of the International Health Regulation was meeting to decide whether the 10th Ebola outbreak in the Demogratic Republic of Congo still constituted a Public Health Emergency of International Concern, a new confirmed case was reported in the city of Beni, the last epicenter of the epidemic. This study aimed to understand the source of this cluster and learn from the implemented control strategies for improved response in the future. Methods: We conducted a combined epidemiological and genomic investigation to understand the origins and dynamics of transmission within this cluster and describe the strategy that successfully controlled the outbreak. Results: Eight cases were identified as belonging to this final cluster. A total of 1028 contacts were identified. Whole-genome sequencing revealed that all cases belonged to the same cluster, the closest sequence to which was identified as a case from the Beni area with symptom onset in July 2019 and a difference of just 31 nucleotides. Outbreak control measures included community confinement of high-risk contacts. Conclusions: This study illustrates the high risk of additional flare-ups in the period leading to the end-of-outbreak declaration and the importance of maintaining enhanced surveillance and confinement activities to rapidly control Ebola outbreaks.